Transcrições para canto e violão de sete canções de Dinorá de Carvalho: processos composicionais e idiomatismo técnico-instrumental - Ranna, Luís Cláudio Cabral da Silveira (2017)
This research proposes the realization of seven transcriptions for voice and guitar of songs by the nationalist composer Dinora de Carvalho (1895-1980). The chosen works are part of various compositional tendencies of the works for voice and piano, resulting from the composer's 46 years of training for this formation, each with its influence. We began our procedure by reflecting on the concerns expressed by transcription scholars, to base the characteristics and limits that were adopted in our intervention. For the technical-instrumental adaptation to the guitar we chose the notes on the transcription by Daniel Wolff and Pedro Rodrigues, allied to the works developed around the thematic language, proposed by Scarduelli and Fernandes. To complement the arguments used, the concepts of Intentio Operis and Overinterpretation proposed by Umberto Eco were used during the text, as well as in the general conception we promote about the work. Flávio Carvalho's master's dissertation runs through the work as essential material for consultation.